الإتجاهات الحديثة للمراجعة الداخلية في المؤسسات الإقتصادية دراسة استطلاعية لعينة من (أكاديميين، محاسبين معتمدين، مراحعين داخليين، وخبراء محاسبين) - الدينوري, محمد سالمي; صالحي, محمد لخضر (جامعة الوادي - University of Eloued, 2021)
This study aims to determine the role of internal auditing in adding value to the Algerian economic institutions, trying projection this study through a survey included 47 samples of (Academics, Certified Public, Accountants Internal Auditors, Accounting Experts), using the questionnaire tool, where "Microsoft Excel 2007" used for unloading data and the Statistical Packages for Social Sciences "SPSS V22" for processing data, analyzing and explaining results. The study concluded that the internal auditing role must be activated in proportion with Stockholder’s needs, who are expecting from the internal auditing department further development, growth and contributing in increasing profits and decreasing costs which leads to the institution’s Progress and prosperity and assisting in success, continuity, achieving goals and adding value to institutions through assurance and consultancy services provided by internal audit department about the effectiveness of internal control system, risk management and governance, in addition to evaluating and auditing the institution functions
Modern trends of internal audit in economical institutions Exploratory study for a sample of (Academics, certified accountants, internal auditors, accounting experts)
مقال
Keywords: مراجعة داخلية؛ إضافة قيمة؛ نظام رقابة داخلية؛ إدارة مخاطر؛ حوكمة.: Internal Audit; Adding Value; Internal Control System; Risk Management; Governance